Two-stage processed high-quality famatinite thin films for photovoltaics. (November 2017) - Chalapathi, U.; Poornaprakash, B.; Cui, Hao; Park, Si-Hyun
Abstract: Famatinite (Cu3 SbS4 ) thin films were prepared by annealing chemically grown Sb2 S3 –CuS stacks in a graphite box at 370–430 °C for 30 min under sulfur and N2 atmospheres. The films grown at 370 °C contain a minor CuSbS2 phase with dominant Cu3 SbS4 . Those films prepared at 400 °C and 430 °C are single-phase Cu3 SbS4 with a tetragonal structure and lattice parameters a = 0.537 nm and b = 1.087 nm and a crystallite size of 25 nm. The grain size of the films increases as the annealing temperature is increased to 400 °C and subsequently decreases. The film morphology is compact and void-free with a grain size of 300–800 nm at 400 °C. The band gap of the films is 0.89 eV. The films exhibited p-type electrical conductivity and a relatively high hole mobility of 14.70 cm 2 V −1 s −1  at 400 °C. Their attractive optoelectronic properties suggest that these films are suitable as solar cell absorber layers. Highlights: Fabrication of high-quality famatinite (Cu3 SbS4 ) thin films by annealing Sb2 S3 -CuS stacks. Films prepared at 400 °C showed good grain growth, compact and uniform morphology. Films exhibited p-type electrical conductivity and higher mobility of 14.70 cm 2  V −1  s −1 .